A Pancasila Perspective On The Clarity Of Legal Formulation Regarding The Single Bar Advocate Organization In Indonesia - Selly, Grees; Ridwan, Ridwan; Setiawan, Arief (Administrative and Environtmental Law Review, 2025)
The ongoing debate over the single bar system for advocate organizations in Indonesia, which remains unresolved in the Draft Law on Amendments to the Advocate Law. Using a normative juridical method with philosophical, comparative, and conceptual approaches, the research analyzes the single bar concept through the lens of Pancasila as the foundation of the rule of law and legal objectives. Findings reveal legal uncertainty and disharmony in implementing the single bar model. While a single bar can strengthen advocates’ roles through standardized ethics and competence, challenges include resistance from existing organizations, maintaining advocate independence, and defining state supervisory roles. The research argues for inclusive, transformative regulations aligned with Pancasila values to balance professionalism and freedom within the legal profession. It concludes that responsive legal politics is essential to clarify the single bar framework in the Advocate Law revision..